Performance of Immobilized-Selected Microorganisms in The Biodegradation of Textile Industry Waste Water - Novarina Irnaning Handayani; Nanik Indah Setianingsih; Misbachul Moenir (Jurnal Riset Teknologi Pencegahan Pencemaran Industri, 2018)
Waste water from textile industry contain pollutant whit in certain concentration. To protect the environment and water bodies, wastewater containing pollutant must be treated before discharging into the environment. Anaerobic biological treatment has been used as a method in treating textile industry waste water. Several factors of conventional anaerobic treatment needs to be repaired in order to improve the performance of treating wastewater. A selected microorganisms as inoculum was expected to increase effectivity of waste water biodegradation. In this study a selected microorganisms was used as inoculum in the form of immobilized and free cells in anaerobic treatment of waste water from textile industry and compared with conventional sludge. Results from this study show that selected-immobilized microorganisms achieved the best performance due to its stability and efficiency in removing pollutant in the waste water. Mean while microorganisms in the form of free cells got the lowest performance in treating waste water, estimated due to its sensitivity of environmental conditions and having low mechanical strength of biomass. Immobilized cells succesfully treated waste water from textile industry, removal of pollutant in suspended solid parameter reached on 93,78% mean while, in oil & grease, BOD5 and COD parameter reached on 99,13%, 81,54% and 64,94% respectively. Pollutant in amonia parameter has not been fully treated in this experiment due to condition of the experiment system was anaerobic instead of aerobic.